Enantioselective N‐Heterocyclic Carbene Catalysis via the Dienyl Acyl Azolium. Issue 17 (24th March 2018) - Gillard, Rachel M.; Fernando, Jared E. M.; Lupton, David W.
Abstract: Herein we report the enantioselective N‐heterocyclic carbene catalyzed (4+2) annulation of the dienyl acyl azolium with enolates. The reaction exploits readily accessible acyl fluorides and TMS enol ethers to give a range of highly enantio‐ and diastereo‐enriched cyclohexenes (most >97:3 er and >20:1 dr). The reaction was found to require high nucleophilicity NHC catalysts with mechanistic studies supporting a stepwise 1, 6‐addition/β‐lactonization. Abstract : 1, 6‐Addition of enolates into the dienyl acyl azolium followed by β‐lactonization provides a diverse array of polycyclic β‐lactones. The reaction proceeds with high enantioselectivity, diastereoselectivity and good yields and represents the first example of enantioselective catalysis using the dienyl acyl azolium, the higher homologue of the α, β‐unsaturated acyl azolium.